2013
DOI: 10.1038/hdy.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate heredity of melanin-based coloration, body mass and immunity

Abstract: The genetic covariation among different traits may cause the appearance of correlated response to selection on multivariate phenotypes. Genes responsible for the expression of melanin-based color traits are also involved in other important physiological functions such as immunity and metabolism by pleiotropy, suggesting the possibility of multivariate evolution. However, little is known about the relationship between melanin coloration and these functions at the additive genetic level in wild vertebrates. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 55 publications
6
52
3
5
Order By: Relevance
“…; Kim et al. ), the role of environmental variance in the expression of melanin‐based traits is striking (Fargallo et al. ; Vergara et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kim et al. ), the role of environmental variance in the expression of melanin‐based traits is striking (Fargallo et al. ; Vergara et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Kim et al. ). To explore the environmental influence, we used the abundance of common voles Microtus arvalis as a proxy of environmental variation, since the abundance of breeding kestrels in our population is sensitive to the interannual fluctuation of vole density (Fargallo et al.…”
Section: Introductionmentioning
confidence: 98%
“…Cross‐fostering experiments in the barn owl ( Tyto alba ) (Roulin & Ducrest, ) and the tawny owl ( Strix aluco ) (Piault et al ., ) also showed that melanin‐based colouration is genetically correlated with numerous phenotypically plastic traits. Similar results are currently being accumulated in different taxa (birds: Kim et al ., ; fish: Wedekind et al ., ; Marie‐Orleach et al ., ; insects: Armitage & Siva‐Jothy, ), strengthening the claim that melanin‐based colouration covaries with phenotypically plastic traits such as immunity, body mass and hormone levels, even in cases in which the expression of this type of colour trait is not, or is only weakly, sensitive to body condition but is strongly genetically inherited. In other words, whether individuals are in good condition (healthy, well fed, whether they invest high or low effort in activities such as reproduction), they produce their genetically programmed colour trait.…”
Section: Introductionmentioning
confidence: 99%
“…Full details of the pedigree statistics can be found in Kim et al . (). The rate of extra‐pair paternity in our study population as well as in other kestrel populations is below 5% (J.A.…”
Section: Methodsmentioning
confidence: 99%